Soarian™ – Workflow Management Applied for Health Care - Haux, R.; Seggewies, C.; Baldauf-Sobez, W.; Kullmann, P.; Reichert, H.; Luedecke, L.; Seibold, H. (Methods of Information in Medicine, 2003)
Objectives: To describe and comment on functionality and architecture of the software product Soarian™ developed by Siemens, to identify key differentiators to related products, and to comment on predecessor systems and beta versions. This has been done in the framework of a conference on health information systems of the IMIA.Methods: Analyzing existing literature. Site visit of a predecessor system at Haukeland Sykehus, Bergen. Pilot of a beta version at the Erlangen University Medical Center, elaborating on major characteristics in discussion rounds.Results: Soarian is a functional comprehensive, clinically oriented software product to support health care processes and to be used for health care professional workstations. It is a software product, designed and written completely new. Three major key differentiators were identified in comparison to related software products: Soarian’s workflow engine, its embedded analytics, and its ‘smart’ user interface. The targeted reduced installation time is stated to be 12 months or less.Conclusions: Soarian has good chances to become one of the major software products for health care professional workstations in the international market to support patient-centered, shared care. Its global design may help to better support and maintain national or language specific versions. The first installations of Soarian will be critical, as they will show how the system will be accepted. To use such software products efficiently, organizational aspects within hospitals as well as between health care institutions have to be considered, e.g. strategic IT planning.
Keywords: Health information systems; clinical information systems; electronic patient record; workflow management; IMIA